Exploring Islamic Social Finance Practices in Muslim Countries Outside ASEAN - Samsudin, Samsudin; Fajrillah, Fajrillah; Lubis, Muhammad Arifin; Lubis, Ali Topan; Siregar, Saparuddin; Juliati Nasution, Yenni Samri (Jurnal Penelitian Medan Agama, 2024)
Islamic social finance, such as zakat, waqf, and alms, plays an important role in supporting social welfare and economic development in Muslim countries. The purpose of this paper is to analyze the implementation of sharia social finance in several Muslim countries outside ASEAN, focusing on the implementation mechanisms, challenges, and impacts of such instruments on social and economic development. Digitalization has changed the way Islamic social finance is managed by increasing accessibility, transparency, and efficiency. The application of technology such as sharia fintech, blockchain, and halal crowdfunding strengthens the role of zakat, waqf, and alms in supporting social welfare in Muslim countries outside ASEAN. This research uses a qualitative method based on literature studies with reference to international journals, reports of Islamic financial institutions, and related secondary data. The focus of the research includes how social financial instruments are managed, the role of governments and private institutions in their implementation, and their contribution to poverty alleviation and social welfare. The main results show that the implementation of sharia social finance in countries such as Turkey or Saudi Arabia has succeeded in improving access to education, health services, and community empowerment. However, there are still challenges in the form of low financial literacy, bureaucratic constraints, and the need to increase cooperation between the public and private sectors. The digitalization of Islamic finance has emerged as a potential solution to increase transparency and efficiency in the management of social funds.